ALGORITHM OF TREATMENT OF CHRONIC CONSTIPATION IN CHILDREN - E.G. Tsymbalova ("Paediatrician" Publishers LLC, 2011)
The article discusses the questions of diagnostical algorithm, classification and approaches to the treatment with laxative drugs, prokinetics and diet. The classification of laxative drugs and their use in pediatric practice are presented.Key words: children, chronic constipation, diagnostics, treatment, laxative drugs.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 108-113)